2002
DOI: 10.1074/jbc.m107694200
|View full text |Cite
|
Sign up to set email alerts
|

Intracellular Sensing of Amino Acids in Xenopus laevis Oocytes Stimulates p70 S6 Kinase in a Target of Rapamycin-dependent Manner

Abstract: Amino acids exert modulatory effects on proteins involved in control of mRNA translation in animal cells through the target of rapamycin (TOR) signaling pathway. Here we use oocytes of Xenopus laevis to investigate mechanisms by which amino acids are "sensed" in animal cells. Small (ϳ48%) but physiologically relevant increases in intracellular but not extracellular total amino acid concentration (or Leu or Trp but not Ala, Glu, or Gln alone) resulted in increased phosphorylation of p70 S6K and its substrate ri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
97
2

Year Published

2003
2003
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 114 publications
(103 citation statements)
references
References 38 publications
4
97
2
Order By: Relevance
“…It has been previously noted that the intracellular level of amino acids can be refractory to changes in the level of extracellular amino acids (74). Studies in rats (75,76) have shown that ethanol and fasting can produce significant changes in the levels of amino acids and related compounds in plasma and various tissues.…”
Section: Discussionmentioning
confidence: 99%
“…It has been previously noted that the intracellular level of amino acids can be refractory to changes in the level of extracellular amino acids (74). Studies in rats (75,76) have shown that ethanol and fasting can produce significant changes in the levels of amino acids and related compounds in plasma and various tissues.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, it is possible that the mTOR signaling pathway is involved in the activation of Adss1 gene expression by glutamine. (41) and Xenopus laevis (42) have highlighted the importance of mTOR in the cellular response to glutamine availability. Recent studies have linked the mTOR pathway with cAMP-induced transcriptional events suggesting an interplay between mTOR and cAMP nutrient signaling pathways (43)(44)(45).…”
Section: Resultsmentioning
confidence: 99%
“…Finally the amino acid sensitive lipid kinase hVPS34 also plays a key role in mTORC1 activation [95] as does the MAPK family member MAP4K3 [96] ( Figure 2). Cell based work has shown that this amino acid sensing system is incredibly sensitive with an ~7% increase in intracellular leucine leading to 50% maximal activation of mTORC1 [97]. Furthermore, only a fraction of maximal mTORC1 activity (~30%) is required to fully saturate muscle protein synthesis [98,99].…”
Section: The Molecular Regulation Of Resistance Training Adaptation mentioning
confidence: 99%